Made-up mouths with preen oil reveal genetic and phenotypic conditions of starling nestlings. (4th April 2022) - Soler, Juan José; Martínez-Renau, Ester; Azcárate-García, Manuel; Ruiz-Castellano, Cristina; Martín, José; Martín-Vivaldi, Manuel
Abstract: Animal coloration results from pigments, nanostructures, or the cosmetic use of natural products, and plays a central role in social communication. The role of cosmetic coloration has traditionally been focused in scenarios of sexual selection, but it could also take place in other contexts. Here, by using spotless starlings ( Sturnus unicolor ) as a model system, we explore the possibility that nestlings cosmetically use their intensely yellow-colored uropygial secretion to signal their genetic and/or phenotypic quality. In agreement with the hypothetical cosmetic use of the uropygial secretion, (i) video recorded nestlings collected secretion with the bill at the age of feathering, (ii) cotton swabs turned to the color of secretion after rubbing with them nestlings' gape, and (iii) gape and skin colorations correlated positively with that of secretion. Furthermore, we found that (iv) secretion coloration has a genetic component, and (v) associated positively with Vitamin E supplementation and (vi) with plasma carotenoid concentration, which highlights the informative value of nestling secretion. Finally, (vii) coloration of begging-related traits and of secretion of nestlings predicted parental feeding preferences. Consequently, all these results strongly suggest that the cosmetic use of colored uropygial secretion might also play a role in parent-offspring communication, complementing or amplifying information provided by the flamboyant colored gapes and skin of nestlings. The use of makeups by offspring for communication with relatives has been scarcely explored and we hope that these results will encourage further investigations in birds and other taxa with parental care. Abstract : Spotless starling nestlings colour their mouths with a yellow secretion that reflects their oxidative status, which in turn influences parental feeding behaviour. We directly observed the cosmetic use of uropigial secretion by nestlings and experimentally demonstrated a link between antioxidants and secretion colour. Moreover, because siblings reared in different starling nests showed similar secretion colour, and because parents prefer to feed nestlings with particular colourations, our results strongly suggest a role of uropygial secretion in parent–offspring communication.